2020
DOI: 10.1155/2020/8890452
|View full text |Cite
|
Sign up to set email alerts
|

AEBP1 Promotes Glioblastoma Progression and Activates the Classical NF-κB Pathway

Abstract: Objective. Our study was aimed at investigating the mechanistic consequences of the upregulation of adipocyte enhancer-binding protein 1 (AEBP1) in glioblastoma (GBM). Methods. The expression of AEBP1 in GBM was assessed by bioinformatics analysis and qRT-PCR; the effects of AEBP1 on GBM cell proliferation, migration, invasion, and tumor growth in vitro and in vivo were detected by a CCK-8 assay, colony formation assay, scratch assay, Transwell assay, and subcutaneous tumor formation, respectively. The activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Adipocyte enhancer binding protein 1 (AEBP1) was rst found in adipocytes and has been reported to be involved in multiple biological processes, including cholesterol homeostasis and in ammation [29], adipogenesis [30], cell differentiation [31]. It is found that AEBP1 can promote the occurrence and development of tumors [32][33][34]. We found that AEBP1 is upregulated in CRC, which is the same as the results of previous studies [34,35].…”
Section: Discussionsupporting
confidence: 87%
“…Adipocyte enhancer binding protein 1 (AEBP1) was rst found in adipocytes and has been reported to be involved in multiple biological processes, including cholesterol homeostasis and in ammation [29], adipogenesis [30], cell differentiation [31]. It is found that AEBP1 can promote the occurrence and development of tumors [32][33][34]. We found that AEBP1 is upregulated in CRC, which is the same as the results of previous studies [34,35].…”
Section: Discussionsupporting
confidence: 87%
“…The Matrigel-Transwell invasion assay, colony formation investigations, and wound healing assays all demonstrated that the capacity of GBM cells to invade was greatly reduced when GRIK1 was inhibited. The molecular mechanisms of GBM growth and invasion are extremely complex and include many factors, such as lactate dehydrogenases [ 36 ], mitogen-activated protein kinase kinase kinase 1(MAP3K1)/c-JUN signaling-axis [ 37 ], Hsa_circ_0072309 [ 38 ], RNA-binding motif protein 8A (RBM8A) [ 9 ], LINC01711 [ 10 ],COL1A2 [ 11 ], adipocyte enhancer-binding protein 1 (AEBP1) [ 39 ], Nucleobindin-2 [ 40 ], the cross-talk between Notch1 signaling and CXCL12/CXCR4 system [ 41 ], PRL1/USP36/Snail2 axis [ 42 ], Zinc finger CCCH-type containing 15 (ZC3H15) [ 43 ], circ_0060055 [ 44 ], and Rhoj/Rac1/PAK signaling [ 45 ], etc.…”
Section: Discussionmentioning
confidence: 99%
“…DNER, a noncanonical Notch ligand, was found to suppress glioma growth by inhibiting the oncogene TOR4A [72] and hindered the growth and induced differentiation of GBM-derived neurospheres [73]. Conversely, TQ treatment resulted in the downregulation of several genes overexpressed in GBM cells, including potential oncogenes like AEBP1, MIAT, GHR, LMO1, ELF3 [74][75][76][77][78], and genes involved in tumor proliferation and migration such as EPHA4, COL3A1, PCDH10, ROBO1, ADAMTS5, PCDH18, ST8SIA1 [79][80][81][82][83][84]. Additionally, TQ significantly downregulated genes associated with poor GBM prognosis, including PCSK5, KCNC1, MXRA5, SEMA3C, MFAP2, MTERF2, KDM2B, FOXP2 [85][86][87][88][89][90][91], indicating TQ's potential in targeting key molecular pathways in GBM.…”
Section: Discussionmentioning
confidence: 99%